Resistance of Lokal, Kara, and Dewata Varieties of Cayenne Pepper (Capsicum Anuum) in Waterlogging Conditions - Iemaaniah, Zuhdiyah Matienatul; Mahrup, Mahrup; Susilowat, Lolita Endang; Kusnarta, IGM; Fahrudin, Fahrudin; Shakila, Nur Asri; Mukminah, Mukminah (Universitas Pekalongan, 2024)
Cayenne pepper is one of the basic commodities and has high economic value. Chili contains capsaicin which gives spicy taste that suitable in various Indonesian food. The high demand of chilies means that this commodity often experiences high selling prices at certain times, especially during the rainy season. The demand that continues to be needed by the community creates great opportunity for chili farmers to continue providing chili on the market. As a plant that can grow well in tropical areas, including Indonesia, chili plants can grow well outside the rainy season. On the other hand, the vertisol soil type, which expands and contracts, requires strong chili plant roots. The rainy season causes plant roots to rot quickly due to waterlogged conditions and plants are easily attacked by pests and diseases. In anticipating failed chili harvest, farmers need planting strategy and selecting quality chili seeds, they can adapt to various environmental conditions. This research was carried out in Sukadana Village using Randomized Block Design field trial method by planting three varieties of chili to find out which variety is most adaptive to waterlogging conditions. The results of the research show that lokal varieties of chili are the most adaptive and resistant to waterlogging conditions.